Preparation method of special high-covering-power titanium dioxide for papermaking
The method enhances the covering power of titanium white powder by incorporating boric acid, nitric acid, and phosphoric acid in the titanium white powder production process, addressing the cost and equipment challenges of existing methods and meeting the high-end paper industry's requirements.
Patent Information
- Application Number
- CN202411843128.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
AI Technical Summary
The current methods for producing high-covering power titanium white powder for the paper industry are costly due to high temperature requirements and equipment demands in the dense silicon phosphorus aluminum inorganic coating process, and there is a shortage of high-end titanium white powder products.
A method involving the preparation of titanium white powder by grinding and milling titanium dioxide slurry, adding a dispersion agent, a boric acid and nitric acid composite solution, phosphoric acid, and aluminum phosphate, followed by pH adjustment and washing to produce a high-covering power titanium white powder suitable for high-end paper applications.
This method effectively enhances the covering power of titanium white powder, reducing its usage in paper production while meeting the high covering power requirements of high-end paper products and improving its optical and chemical properties.
Smart Images

Figure CN119708888A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium dioxide preparation, and in particular to a method for preparing titanium dioxide with high hiding power specially used for papermaking. Background Art
[0002] As a white pigment, titanium dioxide is widely used in coatings, plastics, papermaking, ink, cosmetics, rubber and other fields. The papermaking industry is the third largest user of titanium dioxide, and its development trend also has a significant impact on the titanium dioxide industry.
[0003] At present, there is an oversupply of low-end titanium dioxide in China, while high-end titanium dioxide products are still in short supply. Titanium dioxide is used as a paper filler, mainly in high-grade paper and thin paper. High-end laminated paper requires the use of surface-treated rutile titanium dioxide to meet the requirements of light resistance, heat resistance, and high hiding power.
[0004] In order to meet the quality requirements of high hiding power titanium dioxide in the papermaking field, the hiding power of titanium dioxide of many domestic and foreign manufacturers currently mainly relies on inorganic coating processes such as phosphorus aluminum cerium silicon to meet the quality requirements. However, the dense silicon phosphorus aluminum inorganic coating process has high temperature requirements, even reaching a slightly boiling state, and there is a false thickening phenomenon when the coating material is washed, which has high requirements for production equipment and high production costs. Summary of the invention
[0005] In view of the above problems, the object of the present invention is to provide a method for preparing high hiding power titanium dioxide for papermaking, which can improve the hiding power of titanium dioxide in paper from the source, thereby achieving the purpose of reducing the amount of titanium dioxide used in the papermaking system.
[0006] The technical solution adopted by the present invention is as follows:
[0007] The present invention provides a method for preparing a high hiding power titanium dioxide for papermaking, comprising the following steps:
[0008] S1. Grinding titanium dioxide to prepare titanium dioxide slurry; adding a dispersant solution to the titanium dioxide slurry for slurrying and dispersion;
[0009] S2. Add a composite solution containing barium sulfate and cerium nitrate to the slurry in a certain proportion, and stir at 45-65° C. for 30-60 minutes;
[0010] S3, adding dispersant sodium hexametaphosphate to the slurry for further dispersion;
[0011] S4, raising the slurry temperature to 70°C-85°C, adding phosphoric acid for aging, and then using sodium aluminate solution to adjust the slurry pH to 5.5-7.5;
[0012] S5, cooling the slurry to 50°C-65°C, adding sodium aluminate and stirring to react, and then adjusting the slurry pH to 7.5-8.2 with liquid alkali;
[0013] S6. After washing is qualified, potassium nitrate is added and the product of high hiding power titanium dioxide is obtained by air flow crushing.
[0014] Furthermore, in step S1, the dispersant solution is a composite solution of sodium hexametaphosphate and monoisopropanolamine; wherein the ratio of sodium hexametaphosphate to monoisopropanolamine is 1:0.5; and the added amount of the composite solution of sodium hexametaphosphate and monoisopropanolamine is 0.1-0.5% of the mass of TiO2 in the titanium dioxide slurry.
[0015] Furthermore, in step S1, the dispersant solution is prepared as a composite solution with a solid content of 100-300 g / L.
[0016] Furthermore, in step S1, the titanium dioxide slurry concentration is controlled at 220-300 g / L, the pH is controlled at 9.5-10.5, the slurry viscosity is controlled at less than 50 mpas, and the temperature is controlled at 45-65°C.
[0017] Furthermore, in step S2, in the composite liquid solution containing barium sulfate + cerium nitrate, the ratio of barium sulfate to cerium nitrate is 5:1; the addition amount of the composite liquid solution containing barium sulfate + cerium nitrate is 0.1%-0.5% of the mass of TiO2 in the titanium dioxide slurry, calculated as TiO2.
[0018] Furthermore, in step S3, the added amount of the dispersant sodium hexametaphosphate is 1.5 to 5.0‰ of the mass of TiO2 in the titanium dioxide slurry.
[0019] Furthermore, in step S4, the amount of phosphoric acid added is 1%-5% of the mass of TiO2 in the titanium dioxide slurry calculated as P2O5; and the phosphoric acid is added within 30-60 minutes.
[0020] Furthermore, in step S5, the amount of sodium aluminate added is 3.5%-6.5% of the mass of TiO2 in the titanium dioxide slurry calculated as Al2O3.
[0021] Furthermore, the sodium aluminate is added in the form of a sodium aluminate solution, and the concentration is 100-300 g / L based on alumina.
[0022] Furthermore, in step S6, the washing resistance is greater than 80 ohm·m.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention can effectively improve the hiding power of titanium dioxide products in high-end laminated paper. By adding barium salts, cerium salts, phosphate salts and aluminum salts, the optical defects on the surface of titanium dioxide are filled, the photochemical activity of titanium dioxide is reduced, and the affinity with fibers is increased. The titanium dioxide pigment product produced is particularly suitable for fields such as high-end laminated paper that have special requirements for the high hiding power of titanium dioxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram comparing the hiding power of various embodiments of the present invention and a high-end laminated paper sample. DETAILED DESCRIPTION
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] See attached Figure 1 The present invention provides a method for preparing a high hiding power titanium dioxide for papermaking, and the specific implementation process is as follows:
[0028] S1. Grind titanium dioxide powder to prepare titanium dioxide slurry; add dispersant solution to the titanium dioxide slurry for slurry dispersion; Quality requirements for titanium dioxide primary products: Rotary kiln calcined blocks use a high aluminum, high potassium, and high phosphorus calcined block formula;
[0029] The dispersant solution is a compound solution of sodium hexametaphosphate and monoisopropanolamine; the ratio of sodium hexametaphosphate to monoisopropanolamine is 1:0.5; the addition amount of the compound solution of sodium hexametaphosphate and monoisopropanolamine is 0.1-0.5% of the mass of TiO2 in the titanium dioxide slurry.
[0030] The dispersant solution is prepared as a compound solution with a solid content of 100-300 g / L.
[0031] The titanium dioxide slurry concentration is controlled at 220-300 g / L, the pH is controlled at 9.5-10.5, the slurry viscosity is controlled at less than 50 mpas, and the temperature is controlled at 45-65°C.
[0032] S2. Add a composite liquid solution containing barium sulfate + cerium nitrate to the titanium dioxide slurry in a certain proportion, and stir at 45-65°C for 30-60 minutes; wherein the ratio of barium sulfate to cerium nitrate is 5:1; the amount of the composite liquid solution containing barium sulfate + cerium nitrate added is 0.1%-0.5% of the mass of TiO2 in the titanium dioxide slurry based on TiO2.
[0033] S3. Add sodium hexametaphosphate as a dispersant to the slurry for further dispersion; wherein the amount of sodium hexametaphosphate added is 1.5 to 5.0‰ of the mass of TiO2 in the titanium dioxide slurry.
[0034] After adding the composite liquid solution containing barium sulfate + cerium nitrate, the viscosity of the system increases. The addition of the sodium hexametaphosphate dispersant reduces the viscosity of the solution, ensuring that the composite liquid solution containing barium sulfate + cerium nitrate is evenly dispersed in the titanium dioxide slurry.
[0035] S4, raising the slurry temperature to 70°C-85°C, adding phosphoric acid for aging, and then using sodium aluminate solution to adjust the slurry pH to 5.5-7.5;
[0036] The amount of phosphoric acid added is 1%-5% of the mass of TiO2 in the titanium dioxide slurry calculated as P2O5; the phosphoric acid needs to be added within 30-60 minutes.
[0037] S5, cooling the slurry to 50°C-65°C, adding sodium aluminate and stirring to react, and then adjusting the slurry pH to 7.5-8.2 with liquid alkali;
[0038] The amount of sodium aluminate added is 3.5%-6.5% of the mass of TiO2 in the titanium dioxide slurry calculated as Al2O3; the sodium aluminate is added in the form of sodium aluminate solution, and the concentration is 100-300g / L calculated as alumina.
[0039] S6. Wash the titanium dioxide slurry obtained in the above steps, and the washing resistance is greater than 80 ohm-meter. After the washing is qualified, potassium nitrate is added, and the high hiding power titanium dioxide finished product is obtained by air flow crushing.
[0040] The technical solution of the present invention is further described below by means of specific embodiments:
[0041] Example 1
[0042] S1. Add a dispersant (a composite solution of sodium hexametaphosphate + monoisopropanolamine) to the titanium dioxide slurry for slurry dispersion; wherein the amount of the composite solution of sodium hexametaphosphate and monoisopropanolamine added is 0.1% of the mass of TiO2 in the titanium dioxide slurry.
[0043] S2, a composite liquid solution containing barium sulfate + cerium nitrate, is stirred at 45-65° C. for 30-60 min; wherein the addition amount of the composite liquid solution containing barium sulfate + cerium nitrate is 0.1% of the mass of TiO2 in the titanium dioxide slurry based on TiO2.
[0044] S3. Add dispersant sodium hexametaphosphate composite liquid and disperse again; wherein, the amount of sodium hexametaphosphate composite liquid added is 5.0‰ of the mass of TiO2 in the titanium dioxide slurry.
[0045] S4, raising the slurry temperature to 70°C-85°C, adding phosphoric acid for aging, wherein the amount of phosphoric acid added is 1% of the mass of TiO2 in the titanium dioxide slurry calculated as P2O5, and then adjusting the pH to 6.0-7.5 with sodium aluminate solution;
[0046] S5, cooling the slurry to 50°C-65°C, adding sodium aluminate and stirring to react, wherein the amount of sodium aluminate added is 5% of the mass of TiO2 in the titanium dioxide slurry in terms of Al2O3, and then adjusting the slurry pH to 7.5-8.2 with liquid caustic soda;
[0047] S6. Wash the titanium dioxide slurry obtained in the above steps, and the washing resistance is greater than 80 ohm·m. After the washing is qualified, potassium nitrate is added and the product is obtained by air flow pulverization.
[0048] Example 2
[0049] S1. Add a dispersant (a composite solution of sodium hexametaphosphate + monoisopropanolamine) to the titanium dioxide slurry for slurry dispersion; wherein the amount of the composite solution of sodium hexametaphosphate and monoisopropanolamine added is 0.3% of the mass of TiO2 in the titanium dioxide slurry.
[0050] S2, a composite liquid solution containing barium sulfate and cerium nitrate, is stirred at 45-65° C. for 30-60 min; wherein the addition amount of the composite liquid solution containing barium sulfate and cerium nitrate is 0.25% of the mass of TiO2 in the titanium dioxide slurry in terms of TiO2.
[0051] S3, adding a dispersant sodium hexametaphosphate composite liquid, and dispersing again; wherein the amount of sodium hexametaphosphate composite liquid added is 1.5‰ of the mass of TiO2 in the titanium dioxide slurry;
[0052] S4. The amount of phosphoric acid added is calculated as P2O5, which is 2% of the mass of TiO2 in the titanium dioxide slurry, and then the pH is adjusted to 5.5-7.5 with sodium aluminate solution.
[0053] S5. Cool the slurry to 50-65°C, add sodium aluminate and stir to react, the amount of sodium aluminate added is 6.5% of the mass of TiO2 in the titanium dioxide slurry in terms of Al2O3, and then adjust the slurry pH to 7.5-8.2 with liquid alkali.
[0054] S6. Wash the titanium dioxide slurry obtained in the above steps, and the washing resistance is greater than 80 ohm·m. After the washing is qualified, potassium nitrate is added and the product is obtained by air flow pulverization.
[0055] Example 3
[0056] S1. Add a dispersant (a composite solution of sodium hexametaphosphate + monoisopropanolamine) to the titanium dioxide slurry for slurry dispersion; wherein the amount of the composite solution of sodium hexametaphosphate and monoisopropanolamine added is 0.5% of the mass of TiO2 in the titanium dioxide slurry.
[0057] S2, a composite liquid solution containing barium sulfate and cerium nitrate, is stirred at 45-65° C. for 30-60 min; wherein the addition amount of the composite liquid solution containing barium sulfate and cerium nitrate is 0.5% of the mass of TiO2 in the titanium dioxide slurry in terms of TiO2.
[0058] S3, adding a dispersant sodium hexametaphosphate composite liquid, and dispersing again; wherein the amount of sodium hexametaphosphate composite liquid added is 3.5‰ of the mass of TiO2 in the titanium dioxide slurry;
[0059] S4. The amount of phosphoric acid added is calculated as P2O5 to be 5% of the mass of TiO2 in the titanium dioxide slurry, and then the pH is adjusted to 5.5-7.5 with sodium aluminate solution.
[0060] S5. Cool the slurry to 50-65°C, add sodium aluminate and stir to react, the amount of sodium aluminate added is 3.5% of the mass of TiO2 in the titanium dioxide slurry in terms of Al2O3, and then adjust the slurry pH to 7.5-8.2 with liquid alkali.
[0061] S6. Wash the titanium dioxide slurry obtained in the above steps, and the washing resistance is greater than 80 ohm·m. After the washing is qualified, potassium nitrate is added and the product is obtained by air flow pulverization.
[0062] Through experiments, it was found that Figure 1 As shown, the hiding power of the products prepared in Example 1 (Scheme 1), Example 2 (Scheme 2) and Example 3 (Scheme 3) is close to that of existing foreign high-end laminated paper samples.
[0063] The samples prepared in each embodiment were visually tested for hiding power, and the results are shown in Table 1.
[0064] Table 1 Visual hiding power
[0065] Example 1 Example 2 Example 3 Standard Visual hiding power +0.3 +0.3 +0.2 0
[0066] Matters not described in detail in the present invention are all known technologies.
[0067] The embodiments described above are merely descriptions of preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing high hiding power titanium dioxide for papermaking, characterized in that: The method comprises the following steps: S1. Grinding titanium dioxide to prepare titanium dioxide slurry; adding a dispersant solution to the titanium dioxide slurry for slurrying and dispersion; S2. Add a composite solution containing barium sulfate and cerium nitrate to the slurry in a certain proportion, and stir at 45-65° C. for 30-60 minutes; S3, adding dispersant sodium hexametaphosphate to the slurry for further dispersion; S4, raising the slurry temperature to 70°C-85°C, adding phosphoric acid for aging, and then using sodium aluminate solution to adjust the slurry pH to 5.5-7.5; S5, cooling the slurry to 50°C-65°C, adding sodium aluminate and stirring to react, and then adjusting the slurry pH to 7.5-8.2 with liquid alkali; S6. After washing is qualified, potassium nitrate is added and the product of high hiding power titanium dioxide is obtained by air flow crushing.
2. The method for preparing a high hiding power titanium dioxide for papermaking according to claim 1, characterized in that: In the step S1, the dispersant solution is a composite solution of sodium hexametaphosphate and monoisopropanolamine; wherein the ratio of sodium hexametaphosphate to monoisopropanolamine is 1:0.5; and the amount of the composite solution of sodium hexametaphosphate and monoisopropanolamine added is 0.1-0.5% of the mass of TiO2 in the titanium dioxide slurry.
3. The method for preparing a high hiding power titanium dioxide for papermaking according to claim 1 or 2, characterized in that: In the step S1, the dispersant solution is prepared as a composite solution with a solid content of 100-300 g / L.
4. The method for preparing a high hiding power titanium dioxide for papermaking according to claim 1, characterized in that: In the step S1, the titanium dioxide slurry concentration is controlled at 220-300 g / L, the pH is controlled at 9.5-10.5, the slurry viscosity is controlled at less than 50 mpas, and the temperature is controlled at 45-65°C.
5. The method for preparing a high hiding power titanium dioxide for papermaking according to claim 1, characterized in that: In the step S2, in the composite solution containing barium sulfate + cerium nitrate, the ratio of barium sulfate to cerium nitrate is 5:1; the addition amount of the composite solution containing barium sulfate + cerium nitrate is 0.1%-0.5% of the mass of TiO2 in the titanium dioxide slurry in terms of TiO2.
6. The method for preparing a high hiding power titanium dioxide for papermaking according to claim 1, characterized in that: In the step S3, the added amount of the dispersant sodium hexametaphosphate is 1.5 to 5.0‰ of the mass of TiO2 in the titanium dioxide slurry.
7. The method for preparing a high hiding power titanium dioxide for papermaking according to claim 1, characterized in that: In step S4, the amount of phosphoric acid added is 1%-5% of the mass of TiO2 in the titanium dioxide slurry calculated as P2O5; the phosphoric acid is added within 30-60 minutes.
8. The method for preparing a high hiding power titanium dioxide for papermaking according to claim 1, characterized in that: In the step S5, the amount of sodium aluminate added is 3.5%-6.5% of the mass of TiO2 in the titanium dioxide slurry calculated as Al2O3.
9. The method for preparing a high hiding power titanium dioxide for papermaking according to claim 8, characterized in that: The sodium aluminate is added in the form of a sodium aluminate solution, and the concentration is 100-300 g / L based on alumina.
10. The method for preparing a high hiding power titanium dioxide for papermaking according to claim 1, characterized in that: In step S6, the washed resistance is greater than 80 ohm·m.